Cather Studies, Volume 14 : Unsettling Cather. - Cather Studies, Cather (Cather studies., 2025)
The essays offer compelling ways of seeing and situating Willa Cather's texts--both unsettling and advancing Cather scholarship. Cather was born and spent her first nine years in the Shenandoah Valley of Virginia. Here, as an observant daughter of a privileged white family, Cather first encountered differences and dislocations that remained lively, productive, and sometimes deeply troubling sites of tension and energy throughout her writing life. These essays.